Probabilistic Seismic and Tsunami Hazard Analysis Conditioned on a Megathrust Rupture of the Cascadia Subduction Zone - Park, Hyoungsu; Cox, Daniel T.; Alam, Mohammad Shafiqual; Barbosa, Andre R. (Frontiers in Built Environment, 2017)
This paper presents a framework for a probabilistic hazard assessment for the multi-hazard seismic and tsunami phenomena (PSTHA). For this work, we consider a full-rupture event along the Cascadia Subduction Zone and apply the methodology to the study area of Seaside, Oregon, along the US Pacific Northwest coast. In this work, we show that the annual exceedance probabilities (AEP) of the tsunami intensity measures (IM) are qualitatively dissimilar to the IMs of the seismic ground motion in the study area. Specifically, the spatial gradients for the tsunami IM are much stronger across the length scale of the city owing to the physical differences of energy dissipation of the two mechanisms. Example results of probabilistic seismic hazard analysis (PSHA) and probabilistic tsunami hazard analysis (PTHA) are shown for three observation points in the study area of Seaside. For the seismic hazard, the joint mean annual rate of exceedance shows similar trends for the three observation points, even though there is a large scatter between and . For the tsunami hazard, the joint AEP of hmax and (MF)max shows a high correlation between the two IMs in the study area. The joint AEP at each of the three observation points follows a particular Froude number (Fr) due to the local site-specific conditions locally rather than the distributions of fault slips. The joint probability distribution of hmax and (MF)max throughout the study region falls between 0.1 ≤ Fr < 1.0 (i.e., the flow is subcritical) regardless of return interval (500-, 1,000-, and 2,500-yr). However, the peak of the joint probability distribution with respect to hmax and (MF)max varies with the return interval, and the largest values of hmax and (MF)max were observed with the highest return intervals (2,500 yr) as would be expected. The results of the PSTHA can be the basis for a probabilistic multi-hazard damage assessment and help to understand the uncertainties of the multi-hazard assessments.